2021
DOI: 10.3399/bjgpo.2021.0038
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in general practice in Ireland: a seroprevalence study

Abstract: Background: SARS-CoV-2 antibody testing in community settings may help us better understand the immune response to this virus and therefore help guide public health efforts. Aim: Conduct a seroprevalence study of IgG antibodies in Irish GP clinics. Design and Setting: Participants were 172 staff and 799 patients of 15 general practices in the Midwest region of Ireland. Methods: This seroprevalence study utilised 2 manufacturers’ point-of-care (POC) SARS-CoV-2 IgM-IgG combined antibody tests, offered to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…To estimate prevalence of infectious individuals from reported case incidence data, we assumed that ∼50% of cases were detected. This figure is consistent with the international and national literature (11,(15)(16)(17)(18)(19). Undetected cases are a function of numerous factors including testing capacity, disease incidence, practice regarding referral for testing, and asymptomatic disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To estimate prevalence of infectious individuals from reported case incidence data, we assumed that ∼50% of cases were detected. This figure is consistent with the international and national literature (11,(15)(16)(17)(18)(19). Undetected cases are a function of numerous factors including testing capacity, disease incidence, practice regarding referral for testing, and asymptomatic disease.…”
Section: Discussionsupporting
confidence: 92%
“…Modeling studies have since shown that there was significant under-ascertainment of cases particularly at the peak of the first wave (beginning March 2020 in Ireland) across many countries ( 29 ). Two other Irish sero-prevalence studies have been published: one, conducted in October 2020, found a lower undetected fraction (38%) but was focused on hospital-based healthcare workers ( 18 ) and a second, conducted in June to July 2020, that was based in primary care and found a higher undetected fraction (73%) ( 17 ). For this analysis, a wide range of uncertainty was adopted for the undetected fraction to reflect the limited data available and the fact that the undetected fraction is likely to vary over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that between January and December 2020, seropositivity rates were between 0.4% (March 2020) and 10.2% (October 2020). During the same year, higher seropositivity rates were observed in New York City (May–July 2020; 18+ years; 23.6% [ 10 ] and June–October 2020; 18+ years; 24.3% [ 11 ]), Saudi-Arabia (May–July 2020; 18+ years; 19.3%) [ 12 ], Ireland (June–July 2020; 18+ years; 12.6%) [ 13 ], and Mexico (August–November 2020; 20–39 (27.9%), 40–59 (27.8%) and 60+ (18.6%) years) [ 14 ]. Similar rates were observed in Ethiopia (June–July 2020; 15+ years, 3.2%) [ 15 ], England (April–September 2020; 18–65 years; 5.9%) [ 16 ], Amsterdam, the Netherlands (June and October 2020; 18–70 years, 9.4%) [ 17 ], Germany (May–June 2020; 18+ years; 11.3%) [ 10 ], and the United States (July 2020 (3.5%), December 2020 (11.5%); 16+ years) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%